On the Interplay between Freshwater Content and Hydrographic Conditions in the Arctic Ocean in the 1990s–2010s - Andrey V. Pnyushkov; Genrikh V. Alekseev; Alexander V. Smirnov (Journal of Marine Science and Engineering, 2022)
We investigated liquid freshwater content (FWC) in the upper 100 m layer of the Arctic Ocean using oceanographic observations covering the period from 1990 through 2018. Our analysis revealed two opposite tendencies in freshwater balance—the freshening in the Canada Basin at the mean rate of 2.04 ± 0.64 m/decade and the salinization of the eastern Eurasian Basin (EB) at the rate of 0.96 ± 0.86 m/decade. In line with this, we found that the Arctic Ocean gained an additional 19,000 ± 1000 km3 of freshwater over the 1990–2018 period. FWC changes in the EB since 1990 demonstrate an intermittent pattern with the most rapid decrease (from ~5.5 to 3.8 m) having occurred between 2000 and 2005. The 1990–2018 FWC changes in the upper ocean were concurrent with prominent changes of the thermohaline properties of the intermediate Atlantic Water (AW)—the main source of salt and heat for the Arctic Basin. In the eastern EB, we found a 50 m rise of the upper AW boundary accompanied by a ~0.5 °C increase in the AW core temperature. The close relationship (R > 0.7 ± 0.2) between available potential energy in the layer above the AW and FWC in the eastern EB suggests a positive feedback mechanism that links the amount of freshwater with the intensity of vertical heat and salt exchange in the halocline and upper AW layers. Together with other mechanisms of Atlantification, this feedback creates a complex picture of interactions behind the observed changes in the hydrological and ice regimes of the Eurasian sector of the Arctic Ocean.